2017
DOI: 10.1002/rmb2.12022
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytokine‐induced neutrophil chemoattractant suppresses tumor necrosis factor alpha expression and thereby prevents the follicles from undergoing atresia and apoptosis

Abstract: AimCytokine‐induced neutrophil chemoattractant (CINC/gro) is a CXC family chemokine, similar to interleukin‐8 in rats, and is one of the factors that regulates ovulation. However, the mechanism that regulates atresia of the ovaries postovulation is not clearly defined.MethodsWhether antibody‐blocking of CINC/gro can alter the number of ovulated oocytes and modulate neutrophil infiltration was investigated. The effect of the antibody on the level of inflammatory cytokine production and follicular atresia was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The concentrations of in ammatory factors used in this study were determined based on the concentrations of IL-8 and TNFα measured in the follicular uid of patients, which were able to cause a decrease in LHR expression in mice at the corresponding concentrations, while not causing massive apoptosis of mouse cumulus cells, so we did not explore the effect of the concentration gradient of the two in ammatory factors. Recently, Yu Tanaka et al found that TNF-α expression could be suppressed by inhibiting in ammatory factor-induced neutrophil chemokine activity, which in turn reduced follicular atresia and apoptosis (41), but this study did not investigate the causal relationship between TNF-α and cumulus cell apoptosis at speci c concentrations. In another study, bovine follicular cumulus cells were monitored in vitro using different concentrations of TNF-α (1, 10, 100, and 200 ng/ml) and their survival status was observed, and it was found that 1 ng/ml caused apoptosis and follicular atresia in antral follicular cumulus cells (42).…”
Section: Discussionmentioning
confidence: 87%
“…The concentrations of in ammatory factors used in this study were determined based on the concentrations of IL-8 and TNFα measured in the follicular uid of patients, which were able to cause a decrease in LHR expression in mice at the corresponding concentrations, while not causing massive apoptosis of mouse cumulus cells, so we did not explore the effect of the concentration gradient of the two in ammatory factors. Recently, Yu Tanaka et al found that TNF-α expression could be suppressed by inhibiting in ammatory factor-induced neutrophil chemokine activity, which in turn reduced follicular atresia and apoptosis (41), but this study did not investigate the causal relationship between TNF-α and cumulus cell apoptosis at speci c concentrations. In another study, bovine follicular cumulus cells were monitored in vitro using different concentrations of TNF-α (1, 10, 100, and 200 ng/ml) and their survival status was observed, and it was found that 1 ng/ml caused apoptosis and follicular atresia in antral follicular cumulus cells (42).…”
Section: Discussionmentioning
confidence: 87%
“…The proportion of leukocytes in the medullary zone in the total number was smaller throughout the menstrual cycle. Subsequently, Brännström [32] and Noël et al [45] also found neutrophil density increased remarkably in the thecal layer during ovulation and that IL-8 and Cytokine-induced neutrophil chemoattractant (CINC/gro) expression were responsible for this accumulation [51]. Also, the corpus luteum was rich in neutrophils [32].…”
Section: Neutrophilsmentioning
confidence: 93%
“…Both IL-1β and TNF-α are known to induce ovulation in rats and rabbits (Machelon and Emilie, 1997). The acceleration of ovulation has been reported to occur by neutrophil infiltration into the theca cells layer, which induces IL-1β synthesis and promotes synergy to stimulate ovulation (Tanaka et al, 2017). In mice and humans, IL-1β mRNA levels increase in granulosa cells as the follicle nears rupture (Machelon et al, 1995;Adashi, 1998), emphasizing the role of IL-1β in ovulation.…”
Section: Effects Of Il-1 System Members During Folliculogenesis Oocymentioning
confidence: 99%